International Textbook of Aesthetic Surgery - Scuderi, Nicolò; Toth, Bryant A. (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This two-volume textbook - the result of wide-ranging collaboration among renowned experts in aesthetic surgery from the Americas and Europe - presents state of the art concepts and techniques from across the entire spectrum of cosmetic surgery. It opens with some of the last writings of two of the giants in the discipline, Fernando Ortiz Monasterio and Daniel Marchac, whose contributions set the tone and standard for the rest of the book. In all, there are ten sections covering every aspect of plastic surgery. A very wide range of surgical procedures that can be utilized by the plastic surgeon in training as well as by the established plastic surgeon are described in detail, and in the case of the face, nonsurgical treatments are also fully considered. Further topics include the history of the specialty, legal issues, and anticipated future developments, including regenerative medicine. Numerous beautiful color photographs and skillfully executed illustrations complement the informative text.